2012
DOI: 10.1074/jbc.m111.328377
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Interaction between Proapoptotic Truncated BID (tBID) Protein and Mitochondrial Carrier Homologue 2 (MTCH2) Protein

Abstract: Background: MTCH2 and tBID proteins interact to induce apoptosis in the mitochondrial pathway. Results: Molecular and biophysical studies of the tBID-MTCH2 complex led to two peptides, derived from the tBID-MTCH2 binding interface, which induced cell death. Conclusion: tBID and MTCH2 have two major interaction sites. Peptides derived from the interface are anticancer leads. Significance: The tBID-MTCH2 interaction may be a novel anticancer drug target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…SMAC was used as a control as it is not affected by salt concentration Cardiolipin or MTCH2 can serve as tBID receptors E Raemy et al such compensatory mechanisms, as previous experiments showed that PG cannot substitute for CL in the regulation of MOMP. 13,27 In contrast, MTCH2, which has previously been reported to act as a tBID receptor, 29,41 could compensate for the CL deficit. In favor of this hypothesis, we observed an effect of MTCH2 depletion on tBID recruitment in cells depleted of CL (Figures 5a and b), suggesting that CL and MTCH2 may have compensatory roles in directly binding and recruiting tBID to the MOM, an idea already proposed by others.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…SMAC was used as a control as it is not affected by salt concentration Cardiolipin or MTCH2 can serve as tBID receptors E Raemy et al such compensatory mechanisms, as previous experiments showed that PG cannot substitute for CL in the regulation of MOMP. 13,27 In contrast, MTCH2, which has previously been reported to act as a tBID receptor, 29,41 could compensate for the CL deficit. In favor of this hypothesis, we observed an effect of MTCH2 depletion on tBID recruitment in cells depleted of CL (Figures 5a and b), suggesting that CL and MTCH2 may have compensatory roles in directly binding and recruiting tBID to the MOM, an idea already proposed by others.…”
Section: Discussionmentioning
confidence: 90%
“…In the light of recent studies indicating that MTCH2 may be a receptor for tBID in the MOM, 29,41 we wished to study the effect of MTCH2 downregulation on tBID recruitment to mitochondria, following induction of cell death in WT and CLS1 KO cells. We found that in cells depleted of MTCH2, tBID was normally recruited to mitochondria upon treatment with TRAIL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Arrestin-2 does not have mitochondrial localization signal, and mitochondria contain little FL arrestin-2. However, large proportion of 1-380 localizes to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…This extended tBid loop between helices ␣ 4 and ␣ 5 was shown to be highly flexible and did not show any interaction with the micelles, contrasting to the rigid helical conformation in Bid (Figs. 1 and 4) (60), through which tBid can directly interact with the protein MTCH2 (mitochondrial carrier homologue 2) (36,61). The exposure of this flexible tBid loop enables a scenario where the interaction between tBid and MTCH2 is likely to occur at the mitochondria outer membrane.…”
Section: Distance Restraints (å)mentioning
confidence: 99%